Chinese adolescents' sexual and reproductive health education: A quasi‐experimental study. Issue 1 (5th May 2021) - Ma, Xing; Yang, Yuanyuan; Chow, Ka Ming; Zang, Yuli
Abstract: Objective: This study investigated the effectiveness of an interactive sexual and reproductive health education program in aspects of knowledge, attitudes, and self‐efficacy among adolescents. Design: Quasi‐experimental study underpinned by social cognitive theory. Sample: A stratified cluster sample of 469 students from the two‐branch middle school in a city in eastern China who were assigned to the experimental ( n = 233) and control ( n = 236) groups. Measurements: Students' sexual knowledge, attitudes, and refusal self‐efficacy were assessed before (T0), immediately after (T1), and 1 month after the intervention (T2), respectively. Intervention: Students in the experimental group received two 40‐min sessions of the educational program while the control group received the usual mode of sexual and reproductive health education. Results: Compared with the control group, students in the experimental group acquired more sexual knowledge ( p < .01), and developed more positive sexual attitudes ( p < .05) and stronger sexual self‐efficacy ( p < .05) across the study period. Conclusions: The proposed sexual and reproductive health education program incorporating various interactive activities was effective and could be used for school‐based implementation led by nurses and other health care workers.